2007
DOI: 10.1126/science.1142311
|View full text |Cite
|
Sign up to set email alerts
|

Host Resistance to Lung Infection Mediated by Major Vault Protein in Epithelial Cells

Abstract: The airway epithelium plays an essential role in innate immunity to lung pathogens. Ribonucleoprotein particles primarily composed of major vault protein (MVP) are highly expressed in cells that encounter xenobiotics. However, a clear biologic function for MVP is not established. We report here that MVP is rapidly recruited to lipid rafts when human lung epithelial cells are infected with Pseudomonas aeruginosa, and maximal recruitment is dependent on bacterial binding to the cystic fibrosis transmembrane cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
128
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 32 publications
5
128
0
Order By: Relevance
“…In transgenic CFTR-knockout mice, NF-κB nuclear translocation occurs much later in the airway epithelial cells [28], probably contributing more to the harmful inflammation that ensues in this environment instead of the protective inflammation that occurs when functional CFTR is present. Overall, this scenario wherein WT-CFTR binding of P. aeruginosa leads to protection and failure of this interaction in CF leads to infection is supported by data obtained in numerous in vitro and, importantly, in υivo, studies demonstrating CFTR-dependent responses to P. aeruginosa in a variety of lung epithelial cell lines and in transgenic animals [8][9][10][11][12][27][28][29]31,36]. Thus, it seems that CFTR facilitates bacterial clearance and modulates innate immunity towards P. aeruginosa in lung epithelial cells by being the linchpin needed for coordinating multiple host responses involved in resisting infection and maintaining tissue homeostasis in the long run.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…In transgenic CFTR-knockout mice, NF-κB nuclear translocation occurs much later in the airway epithelial cells [28], probably contributing more to the harmful inflammation that ensues in this environment instead of the protective inflammation that occurs when functional CFTR is present. Overall, this scenario wherein WT-CFTR binding of P. aeruginosa leads to protection and failure of this interaction in CF leads to infection is supported by data obtained in numerous in vitro and, importantly, in υivo, studies demonstrating CFTR-dependent responses to P. aeruginosa in a variety of lung epithelial cell lines and in transgenic animals [8][9][10][11][12][27][28][29]31,36]. Thus, it seems that CFTR facilitates bacterial clearance and modulates innate immunity towards P. aeruginosa in lung epithelial cells by being the linchpin needed for coordinating multiple host responses involved in resisting infection and maintaining tissue homeostasis in the long run.…”
mentioning
confidence: 76%
“…Overall, this scenario wherein WT-CFTR binding of P. aeruginosa leads to protection and failure of this interaction in CF leads to infection is supported by data obtained in numerous in vitro and, importantly, in υivo, studies demonstrating CFTR-dependent responses to P. aeruginosa in a variety of lung epithelial cell lines and in transgenic animals [8][9][10][11][12][27][28][29]31,36]. Thus, it seems that CFTR facilitates bacterial clearance and modulates innate immunity towards P. aeruginosa in lung epithelial cells by being the linchpin needed for coordinating multiple host responses involved in resisting infection and maintaining tissue homeostasis in the long run.A recent approach to determine the molecular components that govern the CFTR-dependent epithelial cell responses to P. aeruginosa has utilized an analysis of host proteins recruited to lipid rafts in human airway epithelial cells within 15 min of infection with P. aeruginosa [36]. About 150 proteins were identified by matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry analysis that were present exclusively in the P. aeruginosa-induced rafts.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…10 MVP expression has also been shown to be induced by histone deacetylase inhibitors such as sodium butyrate, 11 phorbol 12-myristate 13-acetate (PMA) and cytarabine 12 as well as by cytotoxic drugs. [12][13][14] MVP/vaults have been proposed to be important in intracellular transport, [15][16][17] innate immunity 18 and virus infection. 19 Several studies demonstrated that MVP is important in cell signaling [20][21][22] and in cell survival.…”
mentioning
confidence: 99%